Cotton Research 2016
DOI: 10.5772/63796
|View full text |Cite
|
Sign up to set email alerts
|

UV Treatments on Cotton Fibers

Abstract: Ultraviolet (UV) radiations can act in different ways on the functionalization of textiles, through pre-or posttreatments, in order to modify their behavior in dyeing and finishing processes. In cotton fiber, unlike the wool, the UV absorption is not due to any of the structural groups of the normal cellulosic chains and can only be attributed to "impurities" or "faults" bearing carbonyl and/or carboxyl groups. In fact, UV irradiation coupled with mild oxidation can improve some properties of the cotton fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Although the UV treatment time did not seem to affect the strength values in general, it was observed that the strength values of the samples impregnated with the T+H solution decreased with increasing time. This is due to the reduction in strength values as a result of the attack of cellulose by oxidative radicals from H 2 O 2 under UV light [22]. Since NaOH slows down the oxidation process, no significant loss of strength was observed in the processes containing NaOH [21].…”
Section: Tensile Strength Measurements Of Fabricsmentioning
confidence: 99%
“…Although the UV treatment time did not seem to affect the strength values in general, it was observed that the strength values of the samples impregnated with the T+H solution decreased with increasing time. This is due to the reduction in strength values as a result of the attack of cellulose by oxidative radicals from H 2 O 2 under UV light [22]. Since NaOH slows down the oxidation process, no significant loss of strength was observed in the processes containing NaOH [21].…”
Section: Tensile Strength Measurements Of Fabricsmentioning
confidence: 99%
“…Ultraviolet radiation (UV) is often used in cotton pretreatment as it introduces carboxylic groups onto the fabric surface which enhances interaction between the fabric and the dye molecules [ 99 ].…”
Section: Advancements In Mordanting and Substrate Pretreatmentmentioning
confidence: 99%
“…Ultraviolet (UV) radiations can act in different ways on the functionalization of textiles, through pre- or post-treatment, to modify their behavior in dyeing and finishing processes (Ferrero et al , 2016). When the molecules on the surface of synthetic polymers are exposed to the UV lights, excitation and dissociation of the polymeric molecules by the short-wavelength UV radiation occur.…”
Section: Introductionmentioning
confidence: 99%
“…The UV treatments applied in textile, in addition to required specific effects, should also have the following advantages: easy application, not needing expensive and sophisticated equipment; limited treatment costs; and environmentally friendly requirements, for sustainable textile processes (Ferrero et al , 2016). …”
Section: Introductionmentioning
confidence: 99%